Mechanically braked Wingate powers: agreement between SRM, corrected and conventional methods of measurement - Balmer, J.; Bird, S.; Davison, R. R.; Doherty, M.; Smith, P. M. (Journal of Sports Sciences, 2004)
In this study, we assessed the agreement between the powers recorded during a 30 s upper-body Wingate test using three different methods. Fifty-six men completed a single test on a Monark 814E mechanically braked ergometer fitted with a Schoberer Rad Messtechnik (SRM) powermeter. A commercial software package (Wingate test kit version 2.21, Cranlea, UK) was used to calculate conventional and corrected (with accelerative forces) values of power based on a resistive load (5% body mass) and flywheel velocity. The SRM calculated powers based on torque (measured at the crank arm) and crank rate. Values for peak 1 and 5 s power and mean 30 s power were measured. No significant differences (P >0.05) were found between the three methods for 30 s power values. However, the corrected values for peak 1 and 5 s power were 36 and 23% higher (P <0.05) respectively than those for the conventional method, and 27 and 16% higher (P <0.05) respectively than those for the SRM method. The conventional and SRM values for peak 1 and 5 s power were similar (P >0.05). Power values recorded using each method were influenced by sample time (P <0.05). Our results suggest that these three measures of power are similar when sampled over 30 s, but discrepancies occur when the sample time is reduced to either 1 or 5 s.